2018
DOI: 10.1128/jvi.00825-18
|View full text |Cite
|
Sign up to set email alerts
|

PJA1 Coordinates with the SMC5/6 Complex To Restrict DNA Viruses and Episomal Genes in an Interferon-Independent Manner

Abstract: DNA viruses, including hepatitis B virus and herpes simplex virus, induce a series of immune responses in the host and lead to human public health concerns worldwide. In addition to cytokines in the cytoplasm, restriction of viral DNA in the nucleus is an important approach of host immunity. However, the mechanism of foreign DNA recognition and restriction in the cell nucleus is largely unknown. This work demonstrates that an important cellular factor (PJA1) suppresses DNA viruses and transfected plasmids inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Previously, SMC5/6 has been shown to inhibit the transcription of HBV [ 8 , 9 , 10 , 11 ] and HSV-1 [ 11 ]. We questioned whether these antiviral functions of SMC6 and its interactions with HPV E2 indicated that SMC5/6 functions as a repressor of HPV-31 replication or transcription.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, SMC5/6 has been shown to inhibit the transcription of HBV [ 8 , 9 , 10 , 11 ] and HSV-1 [ 11 ]. We questioned whether these antiviral functions of SMC6 and its interactions with HPV E2 indicated that SMC5/6 functions as a repressor of HPV-31 replication or transcription.…”
Section: Resultsmentioning
confidence: 99%
“…SMC6 has been shown to associate with nuclear episomal HBV cccDNA [ 8 ] and HSV-1 DNA [ 11 ], but how SMC5/6 localizes to viral DNA remains unclear. An SMC6 association with HPV genomes has not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The glycine at the final concentration of 125 mM was added for 5 min to terminate cross-linking. The precipitated DNA was purified according to the protocol described in our previous study [19]. The DNA was detected by agarose gel electrophoresis and qRT-PCR.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%